Urgensi Teknik Relaksasi dan Katarsis dalam Menurunkan Stres Pengasuhan Anak - Pridandi, Pirhad (Jurnal Spiritual Healing, 2023)
The presence of a child in a family can have a psychological, social and economic impact. In married life, children are the most awaited thing because they are a gift from God for married couples. The presence of a child does not escape the existence of positive and negative responses. Therefore, many parents experience stress in parenting. This study aims to explain how important relaxation and cathartic techniques are in reducing parenting stress. The research method used is descriptive and qualitative with a literature study approach consisting of two sources, namely primary sources and secondary sources. The results of this study explain that reducing stress on parents in raising children is very important to be considered and studied in depth. In this study, researchers tried to examine how important relaxation and cathartic techniques are in reducing stress caused by parenting. Parenting stress is an adverse psychological and physiological response to the demands of caregiving during the parenting process. This causes tension and anxiety resulting from efforts to adapt to the demands and needs of the child. the importance of relaxation techniques and cathartic techniques to cope with the many parents who are stressed in parenting. Relaxation and cathartic techniques are very possible to be implemented in reducing the stress level of parenting. Stress which refers to a state in which the body becomes tense as it tries to adapt to perform very difficult daily activities. Stress is an unpleasant condition that people perceive as a demand from the condition or beyond their ability to meet these demands